Gagasan Reaktualisasi Teori Pidana Islam dan Relevansinya bagi Pembangunan Hukum di Indonesia - Abdillah, Junaidi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
This paper describes the reform efforts of Islamic Criminal Law theory which initiated by Moslems theorists. Throughout this renewal, the author sees the potential to be the development of the development of Islamic Criminal Law in Indonesia. As far as we know that the transformation of Islamic Criminal Law (fiqh jinayah) into the National Law as still results in theories and epistemological debate in transformation effort. This paper is elaborate research with a juridical-normative approach. The analysis methods used is the general methodical elements such as interpretation and deductive-inductive also personal reflection. This paper concludes: through out the renewal of the theory in the fiqh, jinayah can be developed the theory of contemporary punishment by reactualization Islamic penalization theory. Then Islamic Criminal Law will be more down to be applied in Indonesia